344 Grazing behavior and performance of bred beef heifers grazing stockpiled perennial or annual forages in western Canada. (7th December 2018) - Dahmer, J; McGeough, E; Ominski, K; Crow, G; Cattani, D; Wittenberg, K
Abstract: This study compared grazing behavior and performance of bred beef heifers while stockpile grazing in late fall/early winter. Four stockpiled forage treatments were grazed for 2x28 d grazing periods near Brandon, Manitoba, Canada. Treatments included: 1)Courtney tall fescue (T; Schedonorus arundinaceus (Schreb.) Dumort., formerly Festuca arundinacea )/Fleet meadow brome (M; Bromopsis biebersteinii ) (50:50; TFM), 2)Killarney orchardgrass (O; Dactylis glomeratata )/Algonquin alfalfa (A; Medicago sativa ) (50:50; OGA), 3)Courtney tall fescue/Algonquin alfalfa/Oxley II cicer milkvetch (Ox; Astragalus cicer ) (50:25:25; TAC) and 4)Fusion corn (COR; Zea mays ) in a RCBD with 4 heifers/replicate/ treatment. Heifers were weighed at the beginning and end of each period to determine weight and average daily gain (ADG). A minimum of 3 heifers/treatment wore Lotek 3300L GPS collars to track location every 10 min during the day (05:00-21:00) and 30 min at night (21:00-05:00) during both periods. Windbreak fences were placed on pasture in period 2 when average temperatures and wind speeds were -18.7⁰C and 54 km hr -1, respectively. Time spent grazing (min d -1 ) was measured by time between location fixes. Animal weight did not differ (P=0.3144) between treatments but differed between period 1 (581kg) and period 2 (525kg;P<0.001). In period 1 ADG increased (1.36kg) and decreased in period 2 (-2.00kg;P<0.001). Heifers spent a higher proportion of time each day at the shelter when grazing TFM (0.5362), TAC (0.4307) and OGA (0.3908) compared to COR (0.06813;P<0.001). TFM was higher than TAC and OGA (P<0.05). Heifers spent more time at shelter (P<0.001) at night (0.5047) than during the day (0.2082) for all treatments. In conclusion, cattle grazing corn spent less time at shelter than those grazing perennial treatments, suggesting corn offered sufficient shelter to reduce non-grazing time. However, all cattle lost weight in period 2 once weather conditions declined.